Enhancing employability workshops: Improving placement experiences for medical laboratory science students. - Singh, Indu; Bec King; Cassady, Ian; Hicks, Allan; Kundur, Avinash (Australian Journal of Medical Science, 2025)
The Griffith University Medical Laboratory Science program has developed the Enhancing Employability Workshop, a micro-credentialled initiative in collaboration with industry professionals to enhance student preparedness for clinical placement and future employment. Delivered annually since 2022, the workshop supplements the formal curriculum and delivers industry specialist material that is not feasible to cover in the classroom. Key industry-relevant topics addressed include laboratory information systems, specimen reception, gross sectioning, pre-analytical errors, NATA/ISO15189 standards, 3D virtual reality videos of laboratory automation, cross-disciplinary case studies and employability training. This study evaluates the effectiveness of the workshop by examining (i) student perceptions of the workshop and (ii) industry supervisors' experience with Griffith University placement students. Surveys were administered to students pre- or post-placement and to supervisors during mid-placement reviews. Analysis of the survey responses indicates that the workshop enhances student feeling of preparedness for clinical placement as reported by both students and industry supervisors.